1998
DOI: 10.1021/es980422x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 15N-TNT Residues After an Anaerobic/Aerobic Treatment of Soil/Molasses Mixtures by Solid-State 15N NMR Spectroscopy. 1. Determination and Optimization of Relevant NMR Spectroscopic Parameters

Abstract: Solid-state 15 N NMR was applied to a humic acid, extracted from 15 N-2,4,6-trinitrotoluene (TNT) enriched soil treated in an anaerobic/aerobic composting system to characterize the nitrogen functionality of the transformation products bound to the soil organic material. Signals assignable to aniline derivatives and condensation products were identified, indicating that the anaerobic/aerobic treatment caused a reduction of nitro groups followed by condensation reactions with the soil organic material. Relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 21 publications
(60 reference statements)
3
39
0
Order By: Relevance
“…on May 10, 2018 by guest http://mmbr.asm.org/ subsequent aerated phase eliminated most of the transformation products, possibly by covalent binding to the soil (39,40,134). In tests of the toxic effects of these compounds on human monocytes, leachates of bioremediated soil produced a response similar to that of compost-free of nitroaromatic compounds (41).…”
Section: Applications In Tnt Bioremediationmentioning
confidence: 99%
See 1 more Smart Citation
“…on May 10, 2018 by guest http://mmbr.asm.org/ subsequent aerated phase eliminated most of the transformation products, possibly by covalent binding to the soil (39,40,134). In tests of the toxic effects of these compounds on human monocytes, leachates of bioremediated soil produced a response similar to that of compost-free of nitroaromatic compounds (41).…”
Section: Applications In Tnt Bioremediationmentioning
confidence: 99%
“…After treatment, the reduction metabolites cannot be desorbed from soil by alkaline or acidic hydrolysis or by methanolic extraction, so the authors concluded that metabolites become unavailable for further microbial degradation and mineralization. The covalent binding of reduced metabolites of [ 15 N]TNT to soil organic matter was analyzed by 15 N nuclear magnetic resonance (NMR) spectroscopy (1,134,173); the NMR shifts showed that nitrogen was covalently bound to humic acid as substituted amines and amides, whereas the NMR spectra of silylated humin suggested the formation of azoxy compounds and imine linkages. This indicates immobilization of the aminoaromatic compounds to the soil matrix and can be considered a detoxification process, although information about the long-term fate of these bound metabolites is not available.…”
Section: Applications In Tnt Bioremediationmentioning
confidence: 99%
“…Typically, some combination of aerobic and anaerobic metabolism is required for near complete transformation of TNT carbon and this often starts with denitration prior to ring cleavage (Fiorella and Spain 1997). There are also many reports of incomplete metabolism resulting in the production of intermediates or dead end by-products that may be reactive with natural organic matter (e.g., humics) (Knicker et al 1999, Bruns-Nagel et al 2000. These partial degradation products may be more toxic than the parent compound which may result in increased risk to the ecosystem.…”
Section: Biotic -Secondary Producersmentioning
confidence: 99%
“…There are also many reports of incomplete metabolism resulting in the production of intermediates or dead end by-products that may be reactive with natural organic matter (e.g. humics) (Knicker et al 1999, Bruns-Nagel et al 2000.…”
Section: Biotic -Heterotrophic Bacteriamentioning
confidence: 99%